Analysis Of Delays In Construction Projects: A Study Of Petrochemical Industry - Bagherdaryaii, Saeed (2012)
Delays of a construction project can be defined as the late completion of works as compared to the planned schedule or contract schedule. Projects can be delayed due to number of reasons according to the client,consultant,contractor,force major,or a third party. The objective of this study are to identify the factors that cause delays,the most important reasons that cause delays,the responsible for the delays,the portion of each factor in delays and also the solutions to reduce the effects of delays as much as possible.